Allergic rhinitis and lower airways - Emeryk, Andrzej; Bartkowiak-Emeryk, Małgorzata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
A close relation between allergic rhinitis (AR) and asthma has been reported by many epidemiological and clinical studies. However, the nature of this relation remains unclear. Asthma and AR most frequently coexist in children and adults. AR is a strong risk factor for non-specific bronchial hyperreactivity and is also an independent risk factor for development of asthma. Uncontrolled AR worsens the clinical course of asthma.